SEDIMENT DISTRIBUTION BASED ON GRAIN SIZE ANALYSES IN WEDA BAY, NORTHERN MALUKU - Septriono Hari Nugroho; Abdul Basit (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
An integrated study of sediment distribution was conducted in Weda Bay, Northern Maluku to provide general information on transportation and deposition process based on sediment grain size distribution. The study was conducted during the Weda Bay Expedition using the “Baruna Jaya VII” research vessel in March 13th –22th 2013. Sieving method (granulometric) was used to analyze the grain size. The results indicated that in general the pattern of sea floor sediment distribution was dominated by clay – sand grain-sized. The current speed influenced the sediment transport, deposition, and distribution.  Larger fractions of sediment were quickly settled on the sea floor due to stronger currents around Southern area (Widi islands), meanwhile the lesser fractions of the transported away into other places with weaker currents conditions. Keywords: current, the Weda Bay expedition, granulometric, grain size, sediment distribution